Translating controlled release systems from biomedicine to agriculture - Lee, Paul; Lin, Xin; Khan, Faiz; Bennett, Alison E.; Winter, Jessica O. (Frontiers in Biomaterials Science, 2022)
Sustainable food production is a grand challenge facing the global economy. Traditional agricultural practice requires numerous interventions, such as application of nutrients and pesticides, of which only a fraction are utilized by the target crop plants. Controlled release systems (CRSs) designed for agriculture could improve targeting of agrochemicals, reducing costs and improving environmental sustainability. CRSs have been extensively used in biomedical applications to generate spatiotemporal release patterns of targeted compounds. Such systems protect encapsulant molecules from the external environment and off-target uptake, increasing their biodistribution and pharmacokinetic profiles. Advanced ‘smart’ release designs enable on-demand release in response to environmental cues, and theranostic systems combine sensing and release for real-time monitoring of therapeutic interventions. This review examines the history of biomedical CRSs, highlighting opportunities to translate biomedical designs to agricultural applications. Common encapsulants and targets of agricultural CRSs are discussed, as well as additional demands of these systems, such as need for high volume, low cost, environmentally friendly materials and manufacturing processes. Existing agricultural CRSs are reviewed, and opportunities in emerging systems, such as nanoparticle, ‘smart’ release, and theranostic formulations are highlighted. This review is designed to provide a guide to researchers in the biomedical controlled release field for translating their knowledge to agricultural applications, and to provide a brief introduction of biomedical CRSs to experts in soil ecology, microbiology, horticulture, and crop sciences.